Agustín Basave Fernández del Valle, Tres filósofos alemanes de nuestro tiempo, Universidad Autónoma de Nuevo León, México, 1977, 129 pp - Derisi, Octavio Nicolás (1979)
Fil: Derisi, Octavio Nicolás. Pontificia Universidad Católica Argentina; Argentina